Comparison between intravenous iron sucrose versus oral iron therapy in pregnant women with nutritional anemia: a prospective study - Tandon, Archna; Gupta, Vineeta; Chaudhari, Priyanka; Kumari, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In India, the prevalence of anemia during pregnancy may be as high as 80%. The objective of this study was determining the efficacy of intravenous iron sucrose and oral iron in nutritional anemic antenatal patients, presenting at Shri Guru Ram Rai Institute of Medical and Health Sciences Dehradun, Uttarakhand, India. Methods: The study was carried out in the department of obstetrics and gynecology, Shri Guru Ram Rai Institute of Medical and Health Sciences, Dehradun, Uttarakhand, India single center study was performed on 400 antenatal patients with nutritional anemia gestational age 14 to 36 weeks. Patients were divided in two groups A and B. Group A was treated with intravenous iron sucrose and group B was treated with oral iron sulfate. Results: There was significant improvement in the various hematological parameters in IV sucrose group as compared to patients in oral iron group. There were no significant allergic reactions in IV sucrose group. Conclusions: This study has shown a significant improvement in the iron sucrose group. Iron sucrose is safe and well tolerated.